Urbanization Effects on Biodiversity Revealed by a Two-Scale Analysis of Species Functional Uniqueness vs. Redundancy - Kondratyeva, Anna; Knapp, Sonja; Durka, Walter; Kühn, Ingolf; Vallet, Jeanne; Machon, Nathalie; Martin, Gabrielle; Motard, Eric; Grandcolas, Philippe; Pavoine, Sandrine (Frontiers in Ecology and Evolution, 2020)
Urbanization is one of the most intensive and rapid human-driven factors that threat biodiversity. Finding an indicator of species community responses to urbanization is crucial for predicting the consequences of anthropogenic land cover changes. Here, we develop a framework that relies on functional originality. A species is original or equivalently distinct, regarding its traits, if it possesses rare trait values in a community of species. The most original species have the greatest contributions to the trait diversity of that community. We studied plant species originality, in light of observed changes in the level of species richness, along an urbanization gradient in the region of Paris, France. To evaluate potential impacts of urbanization on species assemblages, we simultaneously considered the local community and regional pool as reference scales where to calculate the originality of each species. Then, for each community, we calculated the mean and skewness of local and regional originalities and the ratio of local to regional originality, providing indication on how functionally diverse a community is, how original it is compared to other communities of the region, how evenly distributed species were in the local and regional functional space, and whether regionally-redundant species become original locally due to limiting similarity. The mean functional originality increased with urbanization at both local and regional scales, although this increase vanished in communities with high species richness. The skewness of originalities increased from zero to positive values with species richness in built-up areas and the ratio of local-to-regional originality increased along the urbanization gradient, except in species-rich communities. Here our results suggest that urban plant communities are composed of both locally and regionally unique urbanophile species, suggesting processes that limit niche overlap to allow species coexistence. In richer communities, these unique species coexist with regionally-redundant species the occurrence of which could be stochastic. Our conceptual framework shows that species originality can inform on environmental processes that influence biodiversity during community assembly. It is flexible enough to be extended to other regions and other contexts complementing diversity metrics in the research of the mechanisms by which human activities impact species assemblages.